2021
DOI: 10.1002/lno.11776
|View full text |Cite
|
Sign up to set email alerts
|

Coupled dynamics of iron, manganese, and phosphorus in brackish coastal sediments populated by cable bacteria

Abstract: Coastal waters worldwide suffer from increased eutrophication and seasonal bottom water hypoxia. Here, we assess the dynamics of iron (Fe), manganese (Mn), and phosphorus (P) in sediments of the eutrophic, brackish Gulf of Finland populated by cable bacteria. At sites where bottom waters are oxic in spring, surface enrichments of Fe and Mn oxides and high abundances of cable bacteria were observed in sediments upon sampling in early summer. At one site, Fe and P were enriched in a thin layer (~3 mm) just below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Manganese oxides found in aquatic systems are typically characterized as poorly crystalline birnessite phases. , Birnessite phases of varying symmetry and structure have also been directly associated with Mn oxide production by bacteria and fungi. , Thus, the Mn­(IV) phases in Siders Pond and found in our dark unfiltered incubation experiment are consistent with those within other natural systems and produced biologically. , Additionally, the occurrence of more reduced Mn oxides like feitknechtite and triclinic birnessite within XAS samples from the pond, which were present in substantial fractions in light unfiltered incubations but not dark unfiltered incubations, indicates that photoreduction likely also plays a role in Mn mineralogy in Siders Pond.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Manganese oxides found in aquatic systems are typically characterized as poorly crystalline birnessite phases. , Birnessite phases of varying symmetry and structure have also been directly associated with Mn oxide production by bacteria and fungi. , Thus, the Mn­(IV) phases in Siders Pond and found in our dark unfiltered incubation experiment are consistent with those within other natural systems and produced biologically. , Additionally, the occurrence of more reduced Mn oxides like feitknechtite and triclinic birnessite within XAS samples from the pond, which were present in substantial fractions in light unfiltered incubations but not dark unfiltered incubations, indicates that photoreduction likely also plays a role in Mn mineralogy in Siders Pond.…”
Section: Discussionsupporting
confidence: 75%
“…The XANES spectrum of this sample (Figure S11) is missing the feature found at ∼6560 eV in the rhodochrosite spectrum as measured by Boulard et al 62 Manganese oxides found in aquatic systems are typically characterized as poorly crystalline birnessite phases. 63,64 Birnessite phases of varying symmetry and structure have also been directly associated with Mn oxide production by bacteria and fungi. 49,57 Thus, the Mn(IV) phases in Siders Pond and found in our dark unfiltered incubation experiment are consistent with those within other natural systems and produced biologically.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Phosphorus is also a key player in the geochemical cycle of TOC (Arif et al, 2021) and is easily fixed or affected by Fe minerals (März et al, 2018). The leading states of phosphorus nutrients in marine sediments include exchangeable, organic, iron-bound, autoecological apatite, detrital, and refractory organic (Fang and Wang, 2021), two-thirds of which are related to poorly crystalline iron and manganese oxides (Hermans et al, 2021). In aquatic and terrestrial systems, the interaction between phosphate and ferric oxides typically involves adsorption/desorption (Boujelben et al, 2008;Yoon et al, 2014), precipitation/dissolution of surface Fephosphate phases (Weng et al, 2012), and precipitation of phosphate in iron (III) oxides (Cheng et al, 2015;März et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although anaerobic mineralization of org‐P continuously sustains sediment pore water with dissolved P that support P release to the water column, a significant proportion of the org‐P present in the surface sediment resists degradation and therefore becomes a major sink for permanent P burial (Mort et al 2010; Hermans et al 2021). Various forms of org‐P differ in resistance to degradation during sediment diagenesis (Ahlgren et al 2006), depending on organic matter supply and its composition, and bottom water O 2 conditions (Defforey and Paytan 2018).…”
mentioning
confidence: 99%
“…Typically, declining org-P contents with depth in Baltic Sea sediments indicate mineralization of org-P in areas where sediment accumulates, either in coastal zones (Lukkari et al 2009;Rydin et al 2011;van Helmond et al 2020) or offshore (Mort et al 2010;Malmaeus and Karlsson 2012). In sediments overlain by oxic bottom water, dissolved phosphate can be temporarily trapped by iron (Fe) and manganese (Mn) (oxy)(hydr)oxides (Conley et al 2002), scavenged by calcium-rich Mn carbonates (Mort et al 2010), precipitated as Mn(II) phosphates (Hermans et al 2019(Hermans et al , 2021, or stored as polyphosphate (poly-P) in prokaryotic organisms (Hupfer et al 1995). Deoxygenation, in turn, can mobilize stored phosphate due to reductive dissolution of P bearing Fe and Mn (oxy)(hydr)oxides (Jilbert et al 2011) and preferential degradation of poly-P (Brock and Schulz-Vogt 2011;Jones et al 2016), and can then be recycled to the bottom water.…”
mentioning
confidence: 99%